2017
DOI: 10.1108/lodj-09-2016-0223
|View full text |Cite
|
Sign up to set email alerts
|

The impact of employees’ values on role engagement

Abstract: In this paper we investigate the manner in which employees' experience of distributive justice moderates the impact of intrinsic and extrinsic values on role engagement. Role engagement is especially important in the healthcare setting, examined here, due to the sector's complexity, changeability and emotionally challenging nature. Using data collected from a survey of employees from a large government health district in Southeast Queensland, Australia, this study examined the determinants of role engagement a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 68 publications
0
1
0
1
Order By: Relevance
“…Sedangkan penghargaan ekstrinsik (extrinsic rewards) meliputi gaji dan upah (salary and wage), jaminan sosial (fringe benefit), penghargaan antar pribadi (interpersonal reward), serta promosi (promotion). Dalam investigasi ini, penelitian difokuskan hanya pada variabel intrinsik karena terkadang reward non komersil lebih berpengaruh signifikan dalam hal komitmen seorang individu (Nazir et al, 2016;Rice et al, 2017). Selain itu, Motivasi yang timbul dari dalam diri yang tinggi sangat baik untuk kemajuan dari sebuah organisasi.…”
unclassified
“…Sedangkan penghargaan ekstrinsik (extrinsic rewards) meliputi gaji dan upah (salary and wage), jaminan sosial (fringe benefit), penghargaan antar pribadi (interpersonal reward), serta promosi (promotion). Dalam investigasi ini, penelitian difokuskan hanya pada variabel intrinsik karena terkadang reward non komersil lebih berpengaruh signifikan dalam hal komitmen seorang individu (Nazir et al, 2016;Rice et al, 2017). Selain itu, Motivasi yang timbul dari dalam diri yang tinggi sangat baik untuk kemajuan dari sebuah organisasi.…”
unclassified
“…(Poon, 2012), and organisational citizenship behaviour (Moorman, 1991;Wong, Wong & Ngo, 2012). The relationship between distributive justice and employee engagement has also been explored, Rice et al (2017) found that distributive justice plays a significant role in positively influencing role engagement above extrinsic rewards. Handayani et al (2017) showed that in a study of 134 employees at an SME distributive justice as well as absorptive capacity had a significant influence on employee engagement, however job design did not have a significant influence on engagement.…”
Section: Distributive Justicementioning
confidence: 99%